1974
DOI: 10.1128/aac.6.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Post-Exposure Prophylaxis of Murine Rabies with Polyinosinic-Polycytidylic Acid and Chlorite-Oxidized Amylose

Abstract: Chlorite-oxidized amylose (COAM), polyinosinic-polycytidylic acid [poly(I:C)], and combinations of the two drugs were evaluated for their interferon-inducing properties and their ability to protect mice against rabies infection. Post-exposure administration of one or two doses (100 μg each) of poly(I:C) significantly protected mice against rabies infection. Pretreatment of mice with COAM 3 h before poly(I:C) stimulation resulted in an enhancement of the interferon response. However, the increased interferon ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Similar results with weaker and delayed IFN-a expression compared with other IFN genes were found in other viruses including influenza A virus and Sendai virus (Marié et al, 1998;Osterlund et al, 2005). The importance of IFNs in response to rabies is illustrated by previous studies that found that the administration of IFN-inducing poly(I-C) resulted in various degrees of protection against RV in mice, hamsters, rabbits and monkeys (Harmon et al, 1974;Hilfenhaus et al, 1975). Similarly, it has been noted that IFN-a/b receptor knockout mice had a higher virus titre than immunologically intact mice after infection with RV (Hooper et al, 1998).…”
Section: Discussionsupporting
confidence: 75%
“…Similar results with weaker and delayed IFN-a expression compared with other IFN genes were found in other viruses including influenza A virus and Sendai virus (Marié et al, 1998;Osterlund et al, 2005). The importance of IFNs in response to rabies is illustrated by previous studies that found that the administration of IFN-inducing poly(I-C) resulted in various degrees of protection against RV in mice, hamsters, rabbits and monkeys (Harmon et al, 1974;Hilfenhaus et al, 1975). Similarly, it has been noted that IFN-a/b receptor knockout mice had a higher virus titre than immunologically intact mice after infection with RV (Hooper et al, 1998).…”
Section: Discussionsupporting
confidence: 75%
“…This is surprising, as COAM was designed to be biodegradable, is active against many viruses, and has a therapeutic index of 300 -500, i.e., a toxicity profile of an order of magnitude better than that of polyI:C [16]. The suggestion that COAM acts like polyI:C and polyacrylates by induction of endogenous IFN is controversial [17][18][19] and was refuted only recently on the basis of in vitro experiments. In sharp contrast with polyI:C, COAM does not induce IFN and, in vitro, acts as a weak virus entry inhibitor [20].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with exogenous homologous or heterologous IFN [175,[183][184][185][186] or inducers of IFN, such as polyriboinosinic-polyribocytidylic acid (poly I:C) [187][188][189], its derivatives containing kanamycin and CaCl 2 (PICKCa) [190] or other structural molecules [191] weaker protection, although the incubation period was prolonged in some treated animals [176,183]. Combinations of drugs, including combinations of IFN-inducers, such as poly I:C, and chlorite-oxidized amylose (COAM), a small inducer of interferon [192], or combinations of rabies vaccines and IFN or IFN inducers [193][194][195] were also effective only when administered close to the time of viral challenge, and the protective effects obtained were variable. Finally, neither clinical improvement nor extension of the incubation period was observed when IFN-based therapy was initiated in a primate model at the onset of clinical symptoms [183,196].…”
Section: Interferons and Interferon-inducing Moleculesmentioning
confidence: 99%